Steps to increase practical applicability of PragTic software. (March 2019) - Tomčala, Jiří; Papuga, Jan; Horák, David; Hapla, Václav; Pecha, Marek; Čermák, Martin
Highlights: The paper Steps to increase practical applicability of PragTic software deals with the parallelization of the fatigue solver PragTic at the node level of the finite element model, and its scalability testing. Because of the intended focus on multiaxial fatigue analysis, the parallelization at the plane level while searching for the critical plane is also discussed. Impact of such changes is clearly demonstrated. Abstract: This paper describes various methods for increasing the computational speed of an existing fatigue solver called PragTic. The paper describes the basic workflow of computational fatigue analysis, including multiaxial fatigue analysis as well. It documents some of the inefficiencies of the original PragTic version, and parallelization and scalability testing of the parallelized PragTic in three different case studies. These studies include a simple model example (hundreds of nodes) and a real world example (millions of nodes). The implemented parallelization techniques are tested using numerical experiments to demonstrate their parallel scalability. As an output of a unique analysis, the number of necessary and feasible evaluated planes in multiaxial analyses is monitored, and the outcome favoring integral methods for the multiaxial fatigue analysis is commented.